The Association between Medicare Advantage Market Penetration and Diabetes in the United States - Howard, Steven W.; Bernell, Stephanie Lazarus; Wilmott, Jennifer; Casim, M. Faizan; Wang, Jing; Pearson, Lindsey; Byler, Caitlin M.; Zhang, Zidong (Frontiers in Public Health, 2015)
The objective of this study is to explore the extent to which managed care market penetration in the U.S. is associated with the presence of chronic disease. Diabetes was selected as the chronic disease of interest due to its increasing prevalence as well as the disease management protocols that can lessen disease complications. We hypothesized that greater managed care market penetration would be associated with: 1) lower prevalence of diabetes, and 2) lower prevalence of diabetes-related comorbidities among diabetics. Data for this analysis came from two sources. We merged Medicare Advantage (MA) market penetration data from the Centers for Medicare and Medicaid Services (CMS) with data from the Medical Expenditure Panel Survey (MEPS) (2004 to 2008). Results suggest that county-level MA market penetration is not significantly associated with prevalence of diabetes or diabetes-related comorbidities. That finding is quite interesting in that managed care market penetration has been shown to have an effect on utilization of inpatient services. It may be that managed care protocols do not offer the same benefits beyond the inpatient setting.